2003
DOI: 10.1016/s0002-9440(10)63467-0
|View full text |Cite
|
Sign up to set email alerts
|

NCAM(CD56) and RUNX1(AML1) Are Up-Regulated in Human Ischemic Cardiomyopathy and a Rat Model of Chronic Cardiac Ischemia

Abstract: Chronic myocardial ischemia is the leading cause of impaired myocardial contractility and heart failure. To identify differentially expressed genes in human ischemic cardiomyopathy (ICM), we constructed a subtracted cDNA library using specimens of ICM compared to normal human heart. Among 100 randomly sequenced clones, seven sequences represented recently identified candidate genes for differential expression in cardiac hypertrophy. A further clone without a known hypertrophy-association coded for the adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…AML1 is a transcription factor that, in cooperation with Ets-1, binds DNA as part of T cell receptor-␣ (TCR␣) enhanceosome (50). Gattenlohner et al (36) showed that AML1 was bound to the promoter region of N-CAM, and both AML1 and N-CAM mRNA expression were upregulated after ischemia of the heart. In denervated EDL muscles, the increase in N-CAM mRNA and protein expression detected in the current study indicates a possible role of AML1 in the upregulation of N-CAM transcription.…”
Section: Discussionmentioning
confidence: 99%
“…AML1 is a transcription factor that, in cooperation with Ets-1, binds DNA as part of T cell receptor-␣ (TCR␣) enhanceosome (50). Gattenlohner et al (36) showed that AML1 was bound to the promoter region of N-CAM, and both AML1 and N-CAM mRNA expression were upregulated after ischemia of the heart. In denervated EDL muscles, the increase in N-CAM mRNA and protein expression detected in the current study indicates a possible role of AML1 in the upregulation of N-CAM transcription.…”
Section: Discussionmentioning
confidence: 99%
“…6). NCAM is a cell adhesion molecule, which affects neural crest cell migration, neuronal fasciculation, neuronal differentiation, and axon guidance (16,17) Interestingly, NCAM is up-regulated by RUNX1, which is expressed on the critical triplicated region of human chromosome 21 and mouse chromosome 16 (11,12). This Furthermore, the fact that the NCAM over expression was clearly present in both neck, heart and ductus venosus region was remarkable, because all of these regions are described to be of importance in the pathophysiology of increased NT in the human fetus (4,18).…”
Section: Discussionmentioning
confidence: 99%
“…NCAM is of special interest, as this protein is regulated by Runt-related gene-1 (RUNX1), which is described as triplicated gene in the trisomy 16 mouse and human trisomy 21 (11,12).…”
mentioning
confidence: 99%
“…The cultures were immunostained with the following primary antibodies: (1) goat anti-collagen type II (1:100; Southern Biotechnology Associates) to detect chondrogenic differentiation, (2) mouse anti-neurofilament 68KD (1:4; Boehringer) for detection of neurons, (3) rabbit anti-FGFR1 (1:100; Santa Cruz; Kubota and Ito, 2000;Sarkar et al, 2001), (4) rabbit anti-FGFR2 (1: 500; Santa Cruz; Kubota and Ito, 2000;Sarkar et al, 2001), (5) rabbit anti-FGFR3 (1:500; Santa Cruz; Kubota and Ito, 2000;Sarkar et al, 2001), and (6) rabbit anti-Hox9 (1:500; Santa Cruz) to detect the expression of the Hox9 paralogous group. This antibody has previously been used in other studies (Gattenlöhner et al, 2003;Okada et al, 2003). Primary antibodies were applied for 12 hr at 4°C.…”
Section: Immunostainingmentioning
confidence: 99%